2006
DOI: 10.1093/qjmed/hcl061
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of coeliac disease in East Dorset 1993-2002: An assessment of the 'coeliac iceberg', and preliminary evidence of case clustering

Abstract: The submerged component of the 'coeliac iceberg' may be diminishing due to increasing case ascertainment, with a projected ratio of undiagnosed to diagnosed cases as low as 1.5:1. Our identification of clustering must be interpreted with caution, but suggests that an additional environmental factor may influence the pathogenesis of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
3
14
0
1
Order By: Relevance
“…Twice as many women were diagnosed as men and the proportion presenting with non-specific symptoms rose dramatically through the study period while the number with diarrhoea declined; these features have been commented on in recent studies. [2][3][4] A further investigation from Derby found that the number of diagnoses was eightfold higher in the quinquennium 2001-2005 compared with 1981-1985. 5 Others have reported an increased prevalence of CD through the years in this country and abroad.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Twice as many women were diagnosed as men and the proportion presenting with non-specific symptoms rose dramatically through the study period while the number with diarrhoea declined; these features have been commented on in recent studies. [2][3][4] A further investigation from Derby found that the number of diagnoses was eightfold higher in the quinquennium 2001-2005 compared with 1981-1985. 5 Others have reported an increased prevalence of CD through the years in this country and abroad.…”
Section: Introductionmentioning
confidence: 96%
“…A study of CD from Dorset, UK, covering the years 1993-2002 revealed an increase from 6 to 13.3 patients per 100 000 population over this period. 2 A report from North America found an increase in prevalence from 11.1 per 100 000 person-years in 2000-2001 to 17.3 in 2008-2010 but only a small number of patients with CD was included. 6 Another series from the USA found a fivefold increase in the prevalence of CD between 1999 and 2008 but only military personnel were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Those that have been published (10,11,12,13,14,15) are very small, have not included all age groups (16), are neither population based nor nationwide (having focussed on, for example, only US military personnel (17) or specific regions of a country (4,18), and have used variable disease definitions (19). Some incidence studies among children have shown a two- to threefold increase in incidence of CD in Denmark and Sweden over a 13-year period (5,8) and another study in Scotland has shown a sixfold increase over 20 years (20), but no general population-based longitudinal data (over multiple decades) are available for all regions of a nation for adult CD.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8], в период с 1993 по 2002 г. отмечено уве-личение заболеваемости с 6 до 13,3 на 100 тыс. [9]. В Северной Америке в период с 2000 по 2001 г. зарегистрировано повышение заболеваемости целиакией с 11,1 до 17,3 на 100 тыс.…”
unclassified